Kekerasan KEKERASAN DALAM NOVEL 00.00 SEPASANG LUKA YANG BERAKHIR DUKA KARYA AMEYLIA FALENSIA: Kritik Sastra - Indah Hapsari; Wika Soviana Devi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
Literary works have several types such as novels, prose (fiction), poetry, drama, romance, and short stories or better known as poetry. In this research, the writer will examine the novel. Novel is a work of prose fiction written in writing, containing elements of imagination and fantasy. Literary criticism is an analysis that examines elements that contain errors. In literary criticism, it is usually more focused on the author's writing in his writings. Literary criticism is a field of literary science and usually applies to the evaluation of literary works. This study uses a qualitative descriptive method with library techniques. In this case, the author uses the novel 00.00 A Pair of Luka that Ends Grief by Ameylia Falensia as research data. By reading it over and over again and determining the results of the research. There is a lot of violence in the novel. Both physical and non-physical violence. We never know someone's mentality, more precisely someone has a different mentality. Victims of violence usually experience trauma and fear in their daily lives and can even do things beyond reason, the perpetrator often ends in death, namely suicide because of the pressures of life that continue to be experienced. Keywords: literary criticism, novel, violence.